KSZTAŁTOWANIE SIĘ POJĘĆ „DIALEKTYZM” I „REGIONALIZM” W DEFINICJACH ENCYKLOPEDYCZNYCH I SŁOWNIKOWYCH - MICHALSKA-GÓRECKA, PAULINA (Slavia Occidentalis, 2020)
The goal of this article is to trace the evolution of understanding two basic concepts in linguistics, namely “dialectism” and “regionalism” with Polish dictionaries and encyclopaedias as the source materials. Excerpts from both general and highly specialised texts have been made. The presented material shows that the definitions of the analysed concepts may vary significantly from one Polish dictionary or encyclopaedia to another. It seems that neither of the definitions exhausts the issue therefore a researcher in charge of territorial differences, in a diachronic and synchronic perspective alike, will have to re-define each time the characterised concepts by means of adjusting their meaning-related scope to his or her own research needs.